From test data to FE code: a straightforward strategy for modelling the structural bonding interface (Fracture and Structural Integrity, 2016)
A straightforward methodology for modelling the cohesive zone (CZM) of an adhesively bonded joint is developed, by using a commercial finite element code and experimental outcomes from standard fracture tests, without defining a damage law explicitly. The in-house developed algorithm implements a linear interpolated cohesive relationship, obtained from literature data, and calculates the damage at each step increment. The algorithm is applicable both to dominant mode I or dominant mode II debonding simulations. The hypothesis of unloading stages occurrence is also considered employing an irreversible behaviour with elastic damaged reloading. A case study for validation is presented, implementing the algorithm in the commercial finite element method (FEM) software Abaqus®. Numerical simulation of dominant mode I fracture loading provides with satisfactory results.
Keywords: Finite element method; Mode I crack; Fracture toughness; Cohesive law; Adhesive bonding